External validation of approaches to prediction of falls during hospital rehabilitation stays and development of a new simpler tool - Angela Vratsistas-Curto; Anne Tiedemann; Daniel Treacy; Stephen R. Lord; Cathie Sherrington (Medical Journals Sweden, 2017)
Objectives: To test the external validity of 4 approaches to fall prediction in a rehabilitation setting (Predict_FIRST, Ontario Modified STRATIFY (OMS), physiotherapists' judgement of fall risk (PT_Risk), and falls in the past year (Past_Falls)), and to develop and test the validity of a simpler tool for fall prediction in rehabilitation (Predict_CM2). Participants: A total of 300 consecutively-admitted rehabilitation inpatients. Methods: Prospective inception cohort study. Falls during the rehabilitation stay were monitored. Potential predictors were extracted from medical records. Results: Forty-one patients (14%) fell during their rehabilitation stay. The external validity, area under the receiver operating characteristic curve (AUC), for predicting future fallers was: 0.71 (95% confidence interval (95% CI): 0.61-0.81) for OMS (Total_Score); 0.66 (95% CI: 0.57-0.74) for Predict_FIRST; 0.65 (95% CI 0.57-0.73) for PT_Risk; and 0.52 for Past_Falls (95% CI: 0.46-0.60). A simple 3-item tool (Predict_CM2) was developed from the most predictive individual items (impaired mobility/transfer ability, impaired cognition, and male sex). The accuracy of Predict_CM2 was 0.73 (95% CI: 0.66-0.81), comparable to OMS (Total_Score) (p = 0.52), significantly better than Predict_FIRST (p = 0.04), and Past_Falls (p < 0.001), and approaching significantly better than PT_Risk (p = 0.09). Conclusion: Predict_CM2 is a simpler screening tool with similar accuracy for predicting fallers in rehabilitation to OMS (Total_Score) and better accuracy than Predict_FIRST or Past_Falls. External validation of Predict_CM2 is required.